Hepatoprotective effect of chewable tablet of Centella asiatica (L.) Urb extractin Wistar rats induced by high fat diets - Akrom; Feri Anggita Hastanto; Nurani, Laela hayu (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2021)
Gotukola or Centella asiatica (L.) Urban contains high flavonoids which well known as fatty liver protector. This study aimed to evaluate the hepatoprotective effect of chewable tablet of C. asiatica (L.) Urb extract (CTCE) in Wistar rats induced by high fat diets. Twenty-one Wistar male rats aged 8-12 weeks with body weight ranging from 100-150 g were used in this study. Rats were randomly divided into seven groups i.e. Group 1 as normal control, rats were given standard food, Group 2 as high fat diets control, rats were induced high fat diets (HFD),Group 3 as positive control, rats were induced HFD and given simvastatin, Group 4 as placebo control, rats were induced HFD and given placebo, Group 5-7 as treatment group, rats were induced HFD and given CTCE at doses of 100, 200 and 300 mg/kg BW, respectively. The HFD induction was conducted for five weeks andthe CTCE was given for one week in the last week of the induction. At the end of the intervention, blood triglyceride levels and SGPT as well SGOT activities were examined. Analysis of variance (ANOVA) with confidence interval of 95% (p<0.05) was applied. The results showed that the HFD induction increased the serum triglyceride levels and SGPT activity. The serum triglyceride levels and SGPT activity of Group 2 were significantly higher than Group 1 (p<0.05). Furthermore, the simvastatin and CTCE administration reduced the serum triglyceride levels and SGPT activity. The serum triglyceride levels and SGPT activity of Group 3, 5, 6and 7 were significantly lower than Group 2 and 4 (p<0.05). In addition, the serum triglyceride levels and SGPT activity of Group 5, 6 and 7 were significantly lower than Group 3 (p<0.05). In conclusion, CTCE can reduce the serum triglyceride levels and SGPT activity in Wistar rats induced by HFD.